Aggregated particles, compositions, coatings, and cosmetics comprising aggregated particles, and method for producing aggregated particles

JP2025030546APending Publication Date: 2025-03-07DENKA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023135933
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0006】 本開示によれば、新規な特性を備える窒化ホウ素の一次粒子の凝集粒子、前記凝集粒子を含む、組成物、塗料及び化粧料並びに前記凝集粒子の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025030546000001_ABST
    Figure 2025030546000001_ABST
Patent Text Reader

Abstract

To provide aggregated particles of boron nitride primary particles having novel properties; compositions, coatings, and cosmetics comprising the aggregated particles; and a method for producing the aggregated particles.SOLUTION: The present invention provides readily disintegrable aggregated particles comprising primary particles of boron nitride. It is preferable that the aggregated particles have the primary particles attached to each other.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to agglomerated particles, compositions, paints and cosmetics containing the agglomerated particles, and methods for producing the agglomerated particles. [Background technology]

[0002] Boron nitride has lubricating properties, high thermal conductivity, and insulating properties, and is widely used as a solid lubricant, a release agent for molten gas and aluminum, and a filler for heat dissipating materials. As boron nitride particles that take advantage of the lubricity and high thermal conductivity that are characteristic of boron nitride, Patent Document 1 describes boron nitride microparticles that are scaly and have a small diameter / thickness ratio (aspect ratio), are submicron sized, and are highly pure and highly crystalline. Patent Document 2 describes spherical boron nitride microparticles of submicron size with high sphericity. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2015 / 122378 [Patent Document 2] International Publication No. 2015 / 122379 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide agglomerated particles of primary particles of boron nitride having novel properties, a composition, a paint, and a cosmetic containing the agglomerated particles, and a method for producing the agglomerated particles. [Means for solving the problem]

[0005] The present disclosure encompasses the following aspects. [First embodiment] Easily disintegratable agglomerated particles comprising primary particles of boron nitride. [Second embodiment] A composition, a paint, and a cosmetic comprising the above aggregated particles. [Third embodiment] A method for producing the above-mentioned agglomerated particles, comprising disintegrating raw material boron nitride particles into primary particles, and obtaining coarse agglomerates of the primary particles. Effect of the Invention

[0006] According to the present disclosure, it is possible to provide agglomerated particles of primary particles of boron nitride having novel properties, compositions, paints, and cosmetics containing the agglomerated particles, and a method for producing the agglomerated particles. [Brief description of the drawings]

[0007] [Figure 1] 3 is an electron microscope photograph showing an example of particles contained in the aggregated particles according to the first embodiment. [Diagram 2] 13 is an optical microscope photograph of the agglomerated particles of Example 12 before the start of compression with a nanoindenter. [Diagram 3] 13 is an optical microscope photograph of the agglomerated particles of Example 12 during compression with a nanoindenter. [Figure 4] 13 is an optical microscope photograph of the agglomerated particles of Example 12 after compression with a nanoindenter. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, an embodiment of the present disclosure will be described in detail, but the scope of the present disclosure is not limited to the embodiment described here, and various modifications can be made within the scope of the present disclosure. Each aspect disclosed in this specification can be combined with any other feature disclosed in this specification. In addition, when multiple upper and lower limit values ​​are described for a specific parameter, any upper and lower limit values ​​among these upper and lower limit values ​​can be combined to form a suitable numerical range. In addition, the lower and / or upper limit values ​​of the numerical range described in this disclosure are numerical values ​​within the numerical range and may be replaced with numerical values ​​shown in the examples. The expression "X to Y" indicating a numerical range means "X or more and Y or less". When a specific description described for one embodiment is also applicable to other embodiments, the description may be omitted in other embodiments. The configurations and combinations thereof in each embodiment are merely examples, and addition, omission, substitution, and other modifications of the configurations are possible as appropriate without departing from the spirit of the present disclosure. The present disclosure is not limited to the embodiments. Each feature disclosed herein may be combined with any other feature disclosed herein.

[0009] [Easily disintegrating agglomerated particles] A first embodiment of the present disclosure relates to easily disintegrable agglomerated particles. The easily disintegrable agglomerated particles according to the first embodiment include primary particles of boron nitride. By containing primary particles of boron nitride, it has the novel property of being easily disintegratable. In this specification, "easily disintegrable" means that the aggregated particles have a property of being easily disintegrated. The "easily disintegrable property" may include, for example, that when the aggregated particles are compressed with a nanointender, the aggregated particles are deformed under a smaller compression load. It may also include that the aggregated particles are broken down into primary particles by a homogenizer treatment when evaluating the average particle size of the aggregated particles. Such "easily disintegrable aggregated particles" are easily obtained, for example, when the primary particles of boron nitride include primary particles of spherical boron nitride. Alternatively, they can also be easily obtained by preparing a coarse aggregate of the primary particles by spray drying after obtaining the primary particles of boron nitride. More specifically, when the agglomerated particles are compressed with a nanointender at a load rate of 0.0015 to 0.015 mN / sec, if the compression load at which the deformation rate of the agglomerated particles is 70% is 0.03 to 3 mN, the agglomerated particles can be said to be "easily disintegratable". Alternatively, when the agglomerated particles are treated with a homogenizer under conditions of a frequency of 20 kHz and a maximum oscillator output of 200 W or more, if 80% by mass or more (preferably 85% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more) of the agglomerated particles disintegrate into primary particles, the agglomerated particles can be said to be "easily disintegratable". In this specification, the term "primary particle" refers to the smallest unit of a particle, a solid particle having boundaries between particles that are recognized as not being able to be divided any further, and particles in which a plurality of primary particles, about 2 to 10 of which are chemically bonded together, are also included in the term "primary particle." The fact that the agglomerated particles are easily disintegrable means that they can be easily broken down into smaller primary particles with a weaker force, and they are also more likely to exhibit the property of dispersing while breaking up in solvents and resins. Such agglomerated particles are expected to be applied to various chemical products, such as cosmetics, paints, and boron nitride molding materials.

[0010] <Average circularity> The aggregated particles according to the first embodiment preferably have an average circularity of 0.6 to 0.9. In one embodiment, the aggregated particles preferably have an average circularity of 0.7 to 0.9, and may be 0.75 to 0.85, or may be 0.80 to 0.85. In one embodiment, the aggregated particles may have an average circularity of 0.77, 0.79, 0.80, 0.82, 0.84, or 0.90, or may be within a range having these upper and lower limits. In this specification, the "average circularity" refers to a value calculated as follows. The image of the aggregated particles (magnification: 500 times, image resolution: 1280 × 1024 pixels) taken with a scanning electron microscope (SEM) is analyzed using image analysis software (e.g., MacView, manufactured by Mountec Co., Ltd.) to calculate the projected area (S) and perimeter (L) of the aggregated particles. The projected area (S) and perimeter (L) are calculated using the following formula: Circularity = 4πS / L 2 The circularity is calculated according to the following formula: The average value of the circularities calculated for 100 or more arbitrarily selected aggregate particles is defined as the average circularity. The aggregated particles according to one embodiment are characterized by a relatively high average circularity, which gives the aggregated particles a round shape and a higher dispersibility when mixed with a solvent, resin, or the like.

[0011] <Average particle size of primary particles> In one embodiment, the average particle size (cumulative by volume (D50)) of the primary particles of boron nitride contained in the agglomerated particles is preferably 0.01 to 1 μm, more preferably 0.1 to 0.8 μm, and even more preferably 0.1 to 0.6 μm. By including primary particles having an average particle size within the above range, the agglomerated particles tend to have better disintegratability. The average particle size of the primary particles of boron nitride can be measured, for example, using a laser diffraction / scattering particle size distribution measuring device (for example, product name "SYNC" manufactured by Microtrack Bell).

[0012] In one embodiment, the aggregated particles are preferably formed by adhering primary particles of boron nitride to each other. By adhering primary particles of boron nitride to each other, the aggregated particles have better disintegration properties than particles in which the primary particles are strongly bonded to each other. "Primary particles of boron nitride are adhered to each other" means that primary particles of boron nitride are physically adhered to each other without the intervention of a binder resin or an oily component. Adhesion without the intervention of a binder resin or an oily component can be confirmed by, for example, not detecting a spectrum derived from a resin or the like used as a binder from the aggregated particles when analyzed using an infrared absorption spectrum measurement method, or not detecting a component derived from a resin or the like from the aggregated particles by a TG-GC / MS method.

[0013] <Volume-based cumulative diameter (D50)> In one embodiment, the aggregated particles have a volume-based cumulative diameter (D50) evaluated by a laser diffraction scattering method without homogenization treatment of preferably 1 to 50 μm, more preferably 2 to 50 μm, even more preferably 3 to 45 μm, even more preferably 3 to 40 μm, and particularly preferably 3 to 30 μm. Since the aggregated particles are in the form of aggregated primary particles of boron nitride, the volume-based cumulative diameter (D50) evaluated by a laser diffraction scattering method without homogenization treatment tends to be a relatively large value such as the above-mentioned range. The aggregated particles may have a volume-based cumulative diameter (D50) of 3.67 μm, 18.8 μm, 20.7 μm, 21.3 μm, 25.3 μm, or 27.8 μm, or may be in a range with these as upper or lower limits. Since the aggregated particles according to this embodiment are easily disintegrable, when homogenized, the aggregated particles tend to become smaller primary particles. Therefore, when homogenization is performed, the D50 tends to become a smaller value.

[0014] "Volume-based cumulative diameter (D50)" (hereinafter simply referred to as particle size (D50)) means the particle size (D50) at which the cumulative frequency in the volume-based arithmetic mean particle size measured by a laser diffraction / scattering particle size distribution measurement method is 50%. The particle size D50 can be measured, for example, using a laser diffraction / scattering particle size distribution measurement device (for example, Microtrack Bell, product name "SYNC"). The "volume-based cumulative diameter (D10)" (hereinafter also simply referred to as particle size (D10)) and the "volume-based cumulative diameter (D90)" (hereinafter also simply referred to as particle size (D90)) also refer to the particle size (D10) and the particle size (D90) at which the cumulative frequency in the volume-based arithmetic mean particle size is 10% and 90%, respectively, as measured by a laser diffraction / scattering particle size distribution measurement method, and can be measured in the same manner as D50. In one embodiment, the particle size (D10) of the agglomerated particles may be 1 to 15 μm or 5 to 15 μm, and the particle size (D90) of the agglomerated particles may be 100 to 300 μm, 100 to 200 μm, or 100 to 180 μm.

[0015] In one embodiment, the primary particles of boron nitride preferably include spherical primary particles of boron nitride. In a more preferred embodiment, the primary particles of boron nitride may be spherical primary particles of boron nitride. By including spherical primary particles of boron nitride, the contact area between particles is likely to be small, and the particles are more easily disintegrable. In addition, the spherical shape of the particles provides better dispersibility in a solvent or resin. Here, whether or not the aggregated particles include spherical primary particles of boron nitride can be determined by, for example, whether or not the primary particles included in the aggregated particles are spherical when the aggregated particles are observed with an electron microscope, as shown in FIG. 1. In addition, "spherical" means that the shape of each primary particle is observed to be a circular or rounded grain shape. Alternatively, "spherical" may mean that the average circularity calculated as follows is 0.8 or more.

[0016] <Average circularity> In one embodiment, the primary particles of spherical boron nitride preferably have an average circularity of 0.8 or more, more preferably 0.85 or more, and even more preferably 0.87 or more. The upper limit of the average circularity is not particularly limited, but may be 1 or less, or 0.95 or less. In this specification, the "average circularity" refers to a value calculated as follows. The image of the primary particle of boron nitride taken with a scanning electron microscope (SEM) (magnification: 10,000 times, image resolution: 1280 x 1024 pixels) is analyzed with image analysis software (e.g., MacView, manufactured by Mountec Co., Ltd.) to calculate the projected area (S) and perimeter (L) of the particle of boron nitride. The projected area (S) and perimeter (L) are used to calculate the following equation: Circularity = 4πS / L 2 The circularity is calculated according to the formula: ##EQU1## The average circularity calculated for 100 or more randomly selected primary particles of boron nitride is defined as the average circularity. The average circularity of the primary particles of boron nitride may be the same as the average circularity of the raw material boron nitride particles described below. For example, when the average circularity of the raw material boron nitride particles is 0.87, the average circularity of the primary particles of boron nitride contained in the aggregated particles can also be 0.87.

[0017] <Deformation ratio> In one embodiment, when the aggregated particles are compressed by a nanointender at a load speed of 0.0015 to 0.015 mN / sec, the compression load at which the deformation rate of the aggregated particles is 70% is preferably 0.03 to 0.3 mN, more preferably 0.03 to 0.28 mN, even more preferably 0.03 to 0.25 mN, and particularly preferably 0.03 to 0.2 mN. Aggregated particles with a compression load of 0.03 to 0.3 mN at a deformation rate of 70% tend to collapse more easily while maintaining a predetermined shape. The compression load at which the deformation rate is 70% may be 0.03 to 0.25 mN, or may be 0.03 to 0.2 mN. The compression load when the deformation rate is 70% may be 0.04 mN, 0.05 mN, 0.06 mN, 0.10 mN, 0.11 mN, 0.15 mN, or 0.23 mN, or may be within a range with these as upper or lower limits. In this specification, the term "compressive load" refers to an external force applied to the surface of an agglomerated particle that acts to push against the surface. The "deformation rate" can be measured by the following method. The particle size of the aggregated particles is measured in advance by image analysis, and then a commercially available nanoindenter is used to measure the load-displacement by the nanoindentation method, and the particle size is calculated according to the following formula. Deformation rate (%): (displacement amount / grain size) x 100 [In the formula, the "displacement amount" is the amount of displacement after the particle to be measured comes into contact with the indenter of the nanoindenter.] Devices capable of carrying out such tests are commercially available; for example, a micro-compression tester (product name "MCT-211") manufactured by Shimadzu Corporation can be used.

[0018] In one embodiment, when the aggregated particles are compressed by a nanointender at a load speed of 0.0015 to 0.015 mN / sec, the compression load at which the deformation rate of the aggregated particles is 90% is preferably 0.2 to 2.0 mN, more preferably 0.2 to 1.8 mN, and even more preferably 0.2 to 1.5 mN. Aggregated particles with a compression load of 0.2 to 2.0 mN at a deformation rate of 90% tend to collapse more easily while maintaining a predetermined shape. The compression load at which the deformation rate is 90% may be 0.2 to 1.8 mN, or may be 0.2 to 1.5 mN. The compression load when the deformation rate is 90% may be 0.32 mN, 0.44 mN, 0.49 mN, 0.52 mN, 0.65 mN, 0.79 mN, or 1.13 mN, or may be within a range with these as upper or lower limits.

[0019] [Compositions, cosmetics and paints containing aggregated particles] The second embodiment of the present disclosure relates to a composition, a cosmetic, and a paint containing the aggregated particles according to the first embodiment. The composition according to the second embodiment may include, but is not limited to, a resin composition, a solvent, and the like, containing the aggregated particles according to the first embodiment. The cosmetic according to the second embodiment may include, but is not limited to, a powder cosmetic, a liquid cosmetic, and the like. In addition, the paint according to the second embodiment may include an outdoor and / or indoor paint. The proportion of aggregated particles in the composition, cosmetic or paint according to the second embodiment is not particularly limited, and can be arbitrarily adjusted within the range of 1 to 99% by mass depending on the application of the composition, cosmetic or paint, or the desired physical properties thereof.

[0020] [Method of manufacturing easily disintegrable aggregated particles] A third embodiment of the present disclosure relates to a method for producing easily disintegrable aggregate particles. The easily disintegrable aggregate particles according to the first embodiment are Breaking down the raw material boron nitride particles into primary particles; and The agglomerates can be produced by a production process that includes obtaining a coarse agglomerate of the primary particles.

[0021] <Raw material: boron nitride particles> Although commercially available boron nitride particles can be used as the raw material boron nitride particles, it is preferable to produce them by the method described in Patent Document 2. That is, a boric acid ester having an ammonia / boric acid ester molar ratio of 1 to 10 and ammonia are reacted in an inert gas stream at 750°C or higher for 30 seconds or less, and then heat-treated in an atmosphere of ammonia gas or a mixed gas of ammonia gas and an inert gas at 1,000 to 1,600°C for 1 hour or more, and then further calcined in an inert gas atmosphere at 1,800 to 2,200°C for 0.5 hours or more to obtain the boric acid ester. An example of the boric acid ester is trimethyl borate.

[0022] The volume-based cumulative diameter (D50) of the raw material boron nitride particles evaluated by a laser diffraction scattering method may be 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, 0.2 μm or more, 0.3 μm or more, or 0.4 μm or more, or 1 μm or less, 0.9 μm or less, 0.8 μm or less, or 0.7 μm or less. In one embodiment, it is preferably 0.01 to 1.0 μm, and more preferably 0.3 to 0.8 μm.

[0023] The raw boron nitride particles are preferably spherical. In one embodiment, the average circularity of the raw boron nitride particles is preferably 0.8 or more, more preferably 0.85 or more, and even more preferably 0.87 or more. The upper limit of the average circularity is not particularly limited, but may be 1 or less, or 0.95 or less. The average circularity of the raw boron nitride can be measured by the same method as the average circularity of the primary particles of boron nitride described above.

[0024] <Disintegrating the raw material boron nitride particles into primary particles> In one embodiment, the disintegration of the raw material boron nitride particles into primary particles preferably includes dispersing the raw material boron nitride particles in a liquid containing cavitation bubbles. As described below, by dispersing in a liquid containing cavitation bubbles, the aggregated raw material boron nitride particles are easily disintegrated into primary particles due to the expansion and contraction force caused by the pressure difference of the bubbles generated by cavitation. By including this step, aggregated particles with better disintegration properties can be obtained. In one embodiment, the disintegration of the raw material boron nitride particles into primary particles may be 80 mass% or more, preferably 90 mass% or more, more preferably 95 mass% or more, and even more preferably 100 mass% of the raw material boron nitride particles are disintegrated into primary particles. In this specification, the term "cavitation bubbles" refers to bubbles that are generated by vaporization when a liquid is in a low pressure state. The generation of cavitation bubbles can be performed using a commercially available device that generates cavitation bubbles by a foaming phenomenon in a liquid caused by reduced pressure or ultrasonic waves. As such a device, it is preferable to use a commercially available powder suction continuous dissolution and dispersion device, and it is particularly preferable to perform a process of circulating the liquid to generate cavitation bubbles. The powder suction continuous dissolution and dispersion device generally has a mechanism for generating a flow rate by an agitator. In one embodiment, the rotation speed of the agitator is preferably 2000 to 10000 rpm, more preferably 4000 to 9000 rpm, even more preferably 4500 to 8000 rpm, and particularly preferably 5000 to 8000 rpm. The rotation speed may be 6000 to 7200 rpm. In one embodiment, the process of generating cavitation bubbles is preferably performed 50 or more times, more preferably 100 or more times, and even more preferably 150 or more times, as the number of cavitation processes calculated from the rotation speed (rpm) of the stirring blades of the device and the discharge volume.

[0025] <Obtaining coarse aggregates of primary particles> The coarse agglomerates of primary particles refer to lumps of boron nitride particles that naturally aggregate during the process of drying boron nitride particles that have been broken down into primary particles as described above, and the coarse agglomerates are larger than the aggregated particles. In one embodiment, obtaining the coarse agglomerates of primary particles preferably includes spray-drying the primary particles (hereinafter referred to as the "spray-drying method"), or recovering the primary particles from the liquid (the liquid containing cavitation bubbles) and then drying them (hereinafter referred to as the "recovery-drying method").

[0026] ·Spray drying method In one embodiment, obtaining the coarse agglomerates preferably includes spray drying the primary particles. When obtaining the coarse agglomerates includes spray drying the primary particles, the coarse agglomerates of the primary particles are obtained and at the same time the coarse agglomerates are broken down, making it easier to obtain the desired agglomerated particles.

[0027] The spray drying is preferably carried out by spray drying a dispersion containing primary particles of boron nitride particles, and more preferably using the dispersion after the above-mentioned cavitation treatment. The solvent of the dispersion may be water, a liquid consisting of only an organic solvent such as ethanol, or a mixed solution of water and an organic solvent. In one embodiment, the viscosity of the dispersion at 25°C is preferably 1 to 10 Pa·s, more preferably 1 to 100 mPa·s. When the viscosity of the dispersion is within the above range, better spraying is possible by spray drying, and the desired aggregated particles are easily obtained.

[0028] The method for drying the dispersion liquid by spray drying is not particularly limited, and any method can be used as long as it can introduce droplets of the dispersion liquid into a heating section of a spray drying device, heat and dry the dispersion liquid in the heating section, and evaporate and dry the dispersion medium to obtain a spray-dried product, which is a dried product of the droplets of the dispersion liquid.

[0029] The spray drying apparatus for performing the spray drying is not particularly limited, and a known apparatus can be suitably used. Examples of the spray drying apparatus include those manufactured by Okawara Seisakusho Co., Ltd. (model number CL-8i), PRIS Co., Ltd. (model number SB39), and Yamato Scientific Co., Ltd. (model number DL410).

[0030] The drying temperature when drying by spray drying is preferably 100 to 200° C., and more preferably 100 to 150° C. When the drying temperature is within the above range, the desired aggregated particles are easily obtained.

[0031] The spray mechanism used in spray drying can be any of a two-fluid nozzle, a one-fluid pressurized nozzle, a three-fluid nozzle, a four-fluid nozzle, an ultrasonic nozzle, or a centrifugal atomizer. Depending on the mechanism selected, various parameters such as the liquid flow rate, gas flow rate, supply gas pressure, and rotation speed can be adjusted to perform spray drying.

[0032] · Recovery · Drying method As a method other than the spray drying method, it is preferable to obtain a coarse agglomerate by recovering primary particles from a liquid containing cavitation bubbles and then drying them. When a recovery and drying method is used to obtain a coarse agglomerate, it is preferable to include disintegrating the coarse agglomerate by the method described below. By including the recovery of primary particles from the liquid and then drying, it is easy to obtain coarse agglomerates that are aggregated to a degree that makes them easy to disintegrate when disintegrating the coarse agglomerates in a subsequent process.

[0033] The primary particles and the aggregated particles can be collected from the liquid containing the cavitation bubbles by filtration, and the collected primary particles and the aggregated particles can be dried by drying the primary particles in a commercially available dryer or oven.

[0034] <Breaking up coarse agglomerates> The coarse agglomerates can be broken down by applying an external force to the coarse agglomerates. In one embodiment, when the coarse agglomerates are obtained by the above-mentioned recovery and drying method, it is preferable to further include a step of loosening the coarse agglomerates by sieving the coarse agglomerates. As the sieve, a commercially available metal mesh sieve or nylon sieve can be used. By sieving with a sieve of a desired mesh size, it becomes easier to obtain agglomerated particles of a desired particle size. As for the mesh size, the opening is preferably 1000 μm or less, more preferably 850 μm or less, and even more preferably 750 μm or less.

[0035] In one embodiment of a method for producing raw material boron nitride particles, coarse agglomerates, and agglomerated particles, the liquid used in the production may be a liquid consisting only of an organic solvent such as ethanol, a mixed solution of water and an organic solvent, or a liquid consisting only of water. In the case of a mixed solution of water and an organic solvent, the water content in the mixed solution is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more.

[0036] Another embodiment of the present disclosure is the use of a composition containing the easily disintegrable aggregate particles as various chemical products or a method of using the same. Preferred examples of chemical products include paints and cosmetics.

[0037] A non-limiting list of exemplary embodiments and combinations of exemplary embodiments of the present disclosure are disclosed below. [1] Easily disintegrable agglomerated particles containing primary particles of boron nitride. [2] The agglomerated particles according to [1], in which the primary particles are adhered to each other. [3] The agglomerated particles according to [1] or [2], wherein when the agglomerated particles are compressed in a nano intender at a load speed of 0.0015 to 0.015 mN / sec, a compression load at which the agglomerated particles have a deformation rate of 70% is 0.03 to 0.3 mN. [4] The agglomerated particles according to any one of [1] to [3], wherein when the agglomerated particles are compressed in a nano intender at a load speed of 0.0015 to 0.015 mN / sec, the compression load at which the agglomerated particles have a deformation rate of 90% is 0.2 to 2.0 mN. [5] The aggregated particles according to any one of [1] to [4], which have a volume-based cumulative diameter (D50) of 1 to 50 μm as evaluated by a laser diffraction scattering method without homogenization. [6] The agglomerated particles according to any one of [1] to [5], wherein the primary particles of boron nitride include spherical primary particles of boron nitride. [7] A composition comprising the aggregated particles according to any one of [1] to [5]. [8] A paint comprising the agglomerated particles described in any one of [1] to [5]. [9] A cosmetic preparation comprising the aggregated particles described in any one of [1] to [5].

[10] A method for producing aggregated particles according to any one of [1] to [6], Breaking down the raw material boron nitride particles into primary particles; and obtaining a coarse agglomerate of the primary particles.

[11] The method for producing agglomerated particles according to

[10] , wherein the disintegrating into primary particles comprises dispersing the raw material boron nitride particles in a liquid containing cavitation bubbles.

[12] The method for producing aggregated particles according to

[11] , wherein obtaining a coarse aggregate of the primary particles includes spray-drying the primary particles, or recovering the primary particles from the liquid and then drying them.

[13] The method for producing agglomerated particles according to any one of

[10] to

[12] , further comprising sieving the coarse agglomerates to break them up. EXAMPLES

[0038] The present invention will be described in more detail below by showing examples, but the interpretation of the present disclosure is not limited to these examples.

[0039] Raw boron nitride particles were prepared by the following procedure. (1) A reaction tube (quartz tube) placed in a resistance heating furnace was heated to 1150°C. Nitrogen gas was passed through trimethyl borate and then introduced into the reaction tube, thereby introducing trimethyl borate into the reaction tube. Next, ammonia gas was directly introduced into the reaction tube. The molar ratio of the amount of ammonia introduced to the amount of trimethyl borate introduced (ammonia / trimethyl borate) was set to 1.8. Trimethyl borate and ammonia were reacted to obtain a precursor of boron nitride particles (white powder). (2) The obtained precursor of boron nitride particles was placed in a boron nitride crucible installed in a resistance heating furnace, and nitrogen gas and ammonia gas were introduced into the reaction tube at flow rates of 10 L / min and 15 L / min, respectively. The reaction tube was heated at 1500°C for 5 hours to obtain a second precursor. (3) The obtained second precursor was placed in a boron nitride crucible and heated in an induction heating furnace in a nitrogen atmosphere at 2000° C. for 5 hours to obtain raw boron nitride particles. The volume-based cumulative diameter (D50) of the raw material boron nitride particles evaluated by a laser diffraction scattering method was 0.62 μm, and the average circularity was 0.87.

[0040] The raw material boron nitride particles were mixed with 1000 cc of ion-exchanged water to obtain the concentration shown in Table 1. Cavitation treatment was carried out using a powder suction continuous dissolution and dispersion device (manufactured by Nihon Spindle Mfg. Co., Ltd., product name "Jet Paster (registered trademark)", model number: JPSS) at a rotation speed (rotation speed of the stirring blade) (rpm) of 7200 rpm and under the conditions shown in Table 1. The "number of treatments" refers to the number of times the treatment solution passes through the agitator blade, calculated from the rotation speed (rpm) of the agitator blade of the powder suction, continuous dissolving and dispersing device and the discharge amount per rotation. After the cavitation treatment, the liquid was filtered through a filter paper with a 0.2 μm pore size to recover the cavitation-treated boron nitride particles. The recovered particles were observed with a scanning electron microscope, and it was confirmed that almost all of the boron nitride particles were in the form of primary particles due to the cavitation treatment under the above conditions.

[0041] The recovered boron nitride particles were treated by the following two methods to obtain agglomerated particles. (Method 1 - Recovery and drying followed by sieving) The collected boron nitride particles were mixed with ion-exchanged water to make a slurry of 10% by weight, and the liquid was filtered through a filter paper with a 0.2 μm pore size and then dried to collect a cake-like coarse aggregate. The obtained coarse aggregate was lightly loosened manually on a nylon mesh using a scraper or the like, and passed through a 20-mesh nylon screen to obtain agglomerated particles.

[0042] (Method 2 - Spray Drying) The collected boron nitride particles were mixed with ion-exchanged water to a concentration of 10% by weight to form a slurry, which was then uniformly sprayed with a four-fluid nozzle (for SE) using a spray dryer (manufactured by GF Corporation, "MDL050M (product name, etc.)") to obtain aggregated particles. The hot air temperatures of the spray dryer were: inlet temperature 200°C, outlet temperature 100°C, nozzle gas flow rate 40NL / min, nozzle gas primary pressure 0.6MPaG, and liquid delivery flow rate 10mL / min.

[0043] [Example 1] <Observation of aggregated particles> A photograph of the agglomerated particles obtained above taken with a scanning electron microscope is shown in Figure 1. As shown in Figure 1, it was confirmed that the agglomerated particles obtained above were in the form of agglomerated raw material boron nitride particles.

[0044] <Confirmation of disintegrability> Six samples were randomly taken from the aggregated particles obtained above (in Table 1, samples 1-5 were obtained by the above method 1, and sample 6 was obtained by the above method 2), 0.1 g was dispersed in 80 mL of ethanol, and the volumetric particle size distribution was measured using a laser diffraction scattering particle size distribution measuring device (manufactured by Microtrack Bell, product name "SYNC") without homogenizing. In this case, the refractive index of ethanol was 1.359, and the refractive index of boron nitride particles was 1.7. From the frequency particle size distribution obtained, the particle size (D10) at which the volumetric cumulative frequency of particles not treated with a homogenizer is 10%, the particle size (D50) at which the volumetric cumulative frequency is 50%, and the particle size (D90) at which the volumetric cumulative frequency is 90% were obtained. The results are shown in Table 1.

[0045] [Table 1]

[0046] Furthermore, 0.1 g of sample 1-6 was dispersed in 80 mL of ethanol and homogenized for 90 seconds at a frequency of 20 kHz and an output of 300 W using a homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., product name "US-300E AMPLITUDE"). After that, the volumetric particle size distribution was measured using a laser diffraction scattering particle size distribution measuring device (manufactured by Microtrack Bell, product name "SYNC"). In this case, the refractive index of ethanol was set to 1.359, and the refractive index of boron nitride particles was set to 1.7. From the frequency particle size distribution obtained, the particle size (D10) at which the volume-based cumulative frequency of the particles treated with the homogenizer is 10%, the particle size (D50) at which the volume-based cumulative frequency is 50%, and the particle size (D90) at which the volume-based cumulative frequency is 90% were obtained. For all of Samples 1-6, the particle size (D10) at which the volume-based cumulative frequency is 10% was in the range of 0.23 to 0.26, the particle size (D50) at which the volume-based cumulative frequency is 50% was in the range of 0.46 to 0.53, and the particle size (D90) at which the volume-based cumulative frequency is 90% was in the range of 1.15 to 1.74. It was found that the agglomerated particles were disintegrated by the homogenizer treatment and were broken down to a particle size similar to or smaller than the particle size (D50 = 0.62 μm) of the raw material boron nitride particles.

[0047] By comparing the particle size in the case where the homogenizer treatment was not performed with the particle size in the case where the homogenizer treatment was performed as shown in Table 1, it was found that the agglomerated particles were disintegrated by the homogenizer treatment to a particle size equal to or smaller than the particle size (D50=0.62 μm) of the raw material boron nitride particles. In other words, it was found that the agglomerated particles according to the first embodiment have a property of being easily disintegrated (easily disintegrable).

[0048] [Examples 2 to 11 and Comparative Example 1] <Average circularity> From the above Samples 1-6, samples of Examples 2 to 11 were further prepared. In addition, as Comparative Example 1, lump boron nitride particles (manufactured by Denka Co., Ltd., product name "Boron Nitride Powder High Thermal Conductivity Lump Grade", average particle size: 41.7 μm) were prepared, and the average circularity was calculated as follows. The images of each aggregated particle taken with a scanning electron microscope (SEM) (magnification: 500 times, image resolution: 1280 × 1024 pixels) were analyzed using image analysis software (manufactured by Mountec Co., Ltd., product name: MacView) to calculate the projected area (S) and perimeter (L) of the aggregated particle. Using the projected area (S) and perimeter (L), the following formula was used: Circularity = 4πS / L 2 The circularity was calculated according to the following formula: The average value of the circularities calculated for 134 arbitrarily selected aggregated particles was defined as the average circularity. The sample correspondence and results are shown in Table 2.

[0049] [Table 2]

[0050] As shown in Table 2, the aggregated particles of the examples satisfying the configuration of the first embodiment had an average circularity within the range of about 0.8 to 0.9. On the other hand, the aggregated boron nitride particles of the comparative example, which do not satisfy the configuration of the first embodiment, had a volume-based cumulative diameter (D50) of 1 to 50 μm as evaluated by a laser diffraction scattering method without homogenization, and the average circularity of the aggregated particles was about 0.6.

[0051] [Examples 12 to 18 and Comparative Example 2] From the above Samples 1-6, samples of Examples 12 to 18 were further prepared, and a nanoindenter (manufactured by Shimadzu Corporation, product name "Micro Compression Tester MCT-211") was used to apply a compressive load to the aggregated particles of each example at the loading rate listed in Table 3, and the compressive load and the displacement at that time were measured (load-displacement measurement by nanoindentation method), and the deformation rate of the particles was calculated. In the measurement, the measurement mode was single indentation measurement, the maximum test force was 1 to 5 mN, the measurement temperature was 23°C, and the indenter used was a MCT truncated cone indenter (φ50 μm). The deformation rate was calculated using the following formula. The particle size of the aggregated particles was measured in advance by image analysis, and then a commercially available nanoindenter was used to measure the load-displacement by the nanoindentation method, and the particle size was calculated according to the following formula. Deformation rate (%): (displacement amount / grain size) x 100 [In the formula, the "displacement amount" is the amount of displacement after the particle to be measured comes into contact with the indenter of the nanoindenter.] Specifically, the measurements were performed according to the following procedure. While checking the microscope image on the optical monitor, the particle size of the target particle was measured with the micrometer. While checking the microscope image, the tip of the indenter was set so that it was above the particle to be measured. The load-displacement measurements were performed at the loading rates shown in Table 3. The compression load at a position where the displacement in the completely compressed state is subtracted by 30% of the grain size was defined as the compression load at a deformation rate of 70%. The compression load at a position where the displacement in the completely compressed state is subtracted by a displacement of 10% of the grain size was defined as the compression load at a deformation rate of 90%. The compressive load when the deformation rate was 70% and the compressive load when the deformation rate was 90% were determined. The results are shown in Table 3. Similarly, as Comparative Example 2, aggregated boron nitride particles (manufactured by Denka Co., Ltd., product name "Boron Nitride Powder High Thermal Conductivity Aggregate Grade", average particle size: 41.6 μm) were prepared and the same measurements were carried out as above to determine the compressive load. The correspondence between the samples and the results are shown in Table 3. Fig. 2 shows an optical microscope photograph of the agglomerated particles according to Example 12 before starting compression with the nanoindenter, Fig. 3 shows an optical microscope photograph of the agglomerated particles according to Example 12 during compression with the nanoindenter, and Fig. 4 shows an optical microscope photograph of the agglomerated particles according to Example 12 after compression with the nanoindenter. In Figs. 2 to 4, the white parts are the agglomerated particles.

[0052] [Table 3]

[0053] As shown in Table 3, the aggregated particles of the examples satisfying the constitution of the first embodiment were significantly deformed by a small compressive load, that is, had a novel property of being easily disintegrable. On the other hand, the comparative example agglomerated boron nitride particles, which did not meet the configuration of the first embodiment, were hard and did not have the disintegratability of the agglomerated particles of the examples, so the loading rate could not be kept constant and deformation could not be confirmed within the range of compressive load as in the examples. As can be seen from the changes in Fig. 2 to Fig. 4, the aggregated particles of the examples satisfying the configuration of the first embodiment were significantly deformed while collapsing from a shape having a predetermined fixed shape when a load was applied, i.e., they had a tendency to easily collapse.

[0054] [Examples 19 to 20 and Comparative Example 3] From the above samples 1-6, samples of Examples 19 and 20 were prepared. Similarly, as Comparative Example 3, chunky boron nitride particles (manufactured by Denka Co., Ltd., product name "Boron Nitride Powder High Thermal Conductivity Chunk Grade", average particle size: 41.6 μm) were prepared. The samples according to Examples 19 and 20 and Comparative Example 3 were evaluated for spreadability as follows using a multi-function static and dynamic friction tester (manufactured by Trinity-Lab, product name "TL-201Ts"). (1) Samples according to Examples 19 and 20 and Comparative Example 3, each having a sample weight of 5.2 mg±0.3 mg and a sample size of 5 mmφ×0.5 mmt, were placed on a 3 cm×15 cm Bioskin (manufactured by Viewlux Corporation, product name “5T#10”). (2) A tactile contactor with a surface structure that mimics a human fingerprint (contact area: 1.5 cm 2 ) was placed on top of the sample, a 0.49 N weight load (equivalent to the pressure acting on a human fingertip during a sensory test) was placed on top of the measurement unit, and then it was confirmed that the spirit level of the measurement unit was level. (3) The spreading distance of the sample was measured when the lower table was moved 100 mm at a speed of 10 mm / sec. The spreading distance was defined as the distance until the line of the sample (white powder) was visually visible. The correspondence of the samples and the results are shown in Table 4.

[0055] [Table 4]

[0056] As shown in Table 4, the agglomerated particles of the examples satisfying the configuration of the first embodiment had a spreading distance of the sample longer than 100 mm. It is understood that the agglomerated particles of the examples satisfying the configuration of the first embodiment have excellent spreading properties under pressure applied to a human fingertip. On the other hand, the comparative example of the aggregated boron nitride particles not satisfying the configuration of the first embodiment was hard, and the spreading distance of the sample was only 23.5 mm, which means that the aggregated particles did not have the spreading properties of the examples.

[0057] From the above results, it can be said that the aggregated particles according to the first embodiment have a novel property of being easily disintegrated, and therefore can impart novel properties to various chemical products by applying them to the products.

Claims

1. Easily disintegrable agglomerated particles containing primary particles of boron nitride.

2. The aggregated particles according to claim 1 , wherein the primary particles are adhered to each other.

3. 3. The agglomerated particles according to claim 1, wherein when the agglomerated particles are compressed in a nano intender at a load speed of 0.0015 to 0.015 mN / sec, a compression load at which a deformation rate of the agglomerated particles is 70% is 0.03 to 0.3 mN.

4. 3. The agglomerated particles according to claim 1, wherein when the agglomerated particles are compressed in a nano intender at a load speed of 0.0015 to 0.015 mN / sec, a compression load at which the deformation rate of the agglomerated particles is 90% is 0.2 to 2.0 mN.

5. 3. The aggregated particles according to claim 1, which have a volume-based cumulative diameter (D50) of 1 to 50 μm as evaluated by a laser diffraction scattering method without homogenization.

6. 3. The agglomerated particles of claim 1 or 2, wherein the boron nitride primary particles comprise spherical boron nitride primary particles.

7. A composition comprising the aggregate particles of claim 1 or 2.

8. A paint comprising the agglomerated particles according to claim 1 or 2.

9. A cosmetic comprising the aggregated particles according to claim 1 or 2.

10. The method for producing aggregated particles according to claim 1 or 2, Breaking down the raw material boron nitride particles into primary particles; and obtaining a coarse agglomerate of the primary particles.

11. The method for producing agglomerated particles according to claim 10 , wherein the disintegrating into primary particles comprises dispersing the raw material boron nitride particles in a liquid containing cavitation bubbles.

12. 12. The method for producing aggregated particles according to claim 11, wherein obtaining the coarse aggregate of the primary particles comprises spray drying the primary particles, or recovering the primary particles from the liquid and then drying them.

13. The method of claim 10, further comprising breaking up the coarse agglomerates by sieving the coarse agglomerates.

Citation Information

Patent Citations

  • Boron nitride particles and production method therefor

    WO2015122378A1

  • Spherical boron nitride particles and production method thereof

    WO2015122379A1